A skill-specific dynamic labour supply and labour demand framework: A scenario analysis for the Western Balkan countries to 2030 - Sandra M. Leitner (The Vienna Institute for International Economic Studies (wiiw), 2021)
This paper pursues a scenario analysis to shed light on past and potential future labour supply and labour demand dynamics of different skill groups in the six Western Balkan countries (WB6). It differentiates between four educational levels (low, medium-general, medium-VET, and high) and looks at a medium-term projection period until 2030. Starting from a baseline scenario, it examines how several different scenarios would affect the employment situation of different skill groups. These scenarios are built on the possible impact which potential labour market policies, education policies, migration flows and policies as well as GDP growth developments and structural change could have on 'surplus' and 'shortage' situations of different skill groups. Simulation results of the baseline scenario show that both labour shortage and excess labour for different skill groups would coexist alongside each other within the projection period. In all WB6 countries, the low educated (given their low activity rates) would experience labour shortages either already within or shortly after the projection period. Similarly, while Med-VETs, Med-GENs and the highly educated would also face labour shortages within or shortly after the projection period in the majority of WB6 countries, in some of these countries, there would also be evidence of growing excess labour, such as among Med-VETs in Montenegro and Kosovo, MedGENs in Kosovo and the highly educated in Bosnia and Herzegovina and Montenegro. Additional scenarios point to important country-specific policy options that can help to mitigate these projected labour market imbalances among different skill groups and, furthermore, contribute to an improved economic development trajectory for these economies.
Keywords: J11; J21; J23; 330; dynamic labour supply-labour demand model; scenario analysis; skill demand by educational groups; skill shortages and surplus; net migration flows; Western Balkan countries